Interleukin 6: at the interface of human health and disease - Grebenciucova, Elena; VanHaerents, Stephen (Frontiers in Immunology, 2023)
Interleukin 6 (IL-6) is a pleiotropic cytokine executing a diverse number of functions, ranging from its effects on acute phase reactant pathways, B and T lymphocytes, blood brain barrier permeability, synovial inflammation, hematopoiesis, and embryonic development. This cytokine empowers the transition between innate and adaptive immune responses and helps recruit macrophages and lymphocytes to the sites of injury or infection. Given that IL-6 is involved both in the immune homeostasis and pathogenesis of several autoimmune diseases, research into therapeutic modulation of IL-6 axis resulted in the approval of a number of effective treatments for several autoimmune disorders like neuromyelitis optica spectrum disorder (NMOSD), rheumatoid arthritis, juvenile idiopathic arthritis, polyarticular juvenile idiopathic arthritis, giant cell arteritis (GCA), and cytokine release syndrome, associated with SARS-CoV2 pneumonia. This review discusses downstream inflammatory pathways of IL-6 expression and therapeutic applications of IL-6 blockade, currently investigated for the treatment of several other autoimmune conditions such as autoimmune encephalitis, autoimmune epilepsy, as well as myelin oligodendrocyte glycoprotein associated demyelination (MOGAD). This review further highlights the need for clinical trials to evaluate IL-6 blockade in disorders such neuropsychiatric lupus erythematosus (SLE), sarcoidosis and Behcet's.